1990
DOI: 10.1152/jappl.1990.69.2.630
|View full text |Cite
|
Sign up to set email alerts
|

Nonrandom variability in respiratory cycle parameters of humans during stage 2 sleep

Abstract: We analyzed breath-to-breath inspiratory time (TI), expiratory time (TE), inspiratory volume (VI), and minute ventilation (Vm) from 11 normal subjects during stage 2 sleep. The analysis consisted of 1) fitting first- and second-order autoregressive models (AR1 and AR2) and 2) obtaining the power spectra of the data by fast-Fourier transform. For the AR2 model, the only coefficients that were statistically different from zero were the average alpha 1 (a1) for TI, VI, and Vm (a1 = 0.19, 0.29, and 0.15, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 0 publications
0
38
0
1
Order By: Relevance
“…PSD of breathing signals can determine which fraction of variational activity is oscillatory at a particular frequency on a breath-to-breath basis. It has been proposed that the standard deviation (SD) for each breath component can be considered as a measure of gross breath-to-breath variability [13,17].…”
Section: Linear Methodsmentioning
confidence: 99%
“…PSD of breathing signals can determine which fraction of variational activity is oscillatory at a particular frequency on a breath-to-breath basis. It has been proposed that the standard deviation (SD) for each breath component can be considered as a measure of gross breath-to-breath variability [13,17].…”
Section: Linear Methodsmentioning
confidence: 99%
“…The classical view of stable homeostasis is that, via bilateral negative feedback, a physiological control system seeks to maintain its trajectory within a neighborhood of a single X. In this case, the dynamics local to X depend primarily on the linearization of f: dX t /dX t Ϫ d for d ϭ 1,...,D; although the assumption is often unstated, many analysts proceed on the assumption that higher-order terms on X t are negligible, i.e., d n X t /d X t Ϫ d n Ϸ 0 for all d Ͼ 0 and n Ͼ 1 (1,13,14,23,26,36). Inasmuch as this can result in biased parameter estimates for physiological systems with questionable local stability (e.g., patients with pathological homeostasis), a simple model-independent statistical method is needed to quantify deviations from linearity.…”
Section: Statistical Methods and Definition Of Termsmentioning
confidence: 99%
“…For nonlinear systems with nonzero second derivatives, r 2 depends also on the SNR, with system memory generally increasing with level of noise (23). Less familiar, however, is the concept that the mean and skewness of the output signal can also be viewed in terms of deterministic and random components.…”
Section: Dynamic Changes In Mean Skewness and Coefficient Of Determmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive variability has also been reported as a sign of deleterious instability [6,7] , and an equilibrium is probably necessary [8] . Using time-series analysis, it has been shown that the magnitude of a component of one breath is positively correlated with the magnitude of the component of the preceding breath [9][10][11][12] . This observation that a given breath is followed by breaths with similar characteristics has been called 'shortterm memory' [10] , despite the fact that it does not necessarily originate from a neural mechanism.…”
Section: Introductionmentioning
confidence: 99%